The involvement of the synaptic vesicle cycle in homocysteine induced neurotoxicity in vitro and in vivo - Meng Wang; Xiaoshan Liang; Keqing Jin; Yinyue Liu; Suhui Luo; Qiang Zhang; Xuan Wang; Zhiping Dong; Xumei zhang (Scientific Reports)
Abstract Homocysteine (Hcy), a sulfur-containing amino acid derived from methionine, has been shown to be a significant and modifiable risk factor for various neurological disorders, including stroke, Parkinson’s disease, Alzheimer’s disease, and elderly depression. However, there is currently a lack of comprehensive understanding regarding the molecular mechanisms underlying Hcy-induced neurotoxicity. Therefore, this study aimed to establish rat and cell models of Hcy intervention in order to elucidate the underlying mechanism of neurotoxicity. Our research findings demonstrate that Hcy induces depressive - like symptoms in normal Sprague-Dawley rats. Pathological damage and apoptosis were detected in the DG, CA3, and CA1 regions of the hippocampus, along with the cortical area. Moreover, synaptic structural impairment was observed within the hippocampal. Simultaneously, Hcy promotes neuronal apoptosis and LDH leakage in mouse neuroblastoma (N2a) cells. Furthermore, we conducted mRNA microarray analysis to investigate differences in mRNA expressions and utilized Gene ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analysis for gene function annotations in Hcy-treated N2a cells. The results highlighted significant alterations in 457 mRNAs in the Hcy-treated group compared to the Control group. Among the differentially expressed genes (DEGs), a total of 155 were found to be significantly up-regulated, while the remaining 302 were down-regulated. Furthermore, it was observed that four genes (snap25, cplx1, slc32a1 and atp6v1e2) related to the synaptic vesicle cycle exhibited decreased expression in Hcy-treated N2a cells compared to the Control group. The expression levels of these four genes, as well as their corresponding proteins, were subsequently confirmed using RT-qPCR and western blot analysis, respectively. In conclusion, this study shed light on the detrimental impact of hyperhomocysteinemia on the nervous system, particularly with regard to the synaptic vesicle cycle.